Web-Based Decision Support System for Family Hope Program (PKH) Beneficiaries in Dharmasraya Using the Simple Additive Weighting (SAW) Method.: Sistem Pendukung Keputusan Penerima Bantuan Program Keluarga Harapan (PKH) di Dharmasraya Menggunakan Metode Simple Additive Weighting (SAW) Berbasis Web - Azzahra Hafidza Melco; Elinda Revita; Evi Yulia Susanti (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
The Family Hope Program (PKH) is a social assistance program aimed at improving the welfare of low-income families. The process of determining beneficiaries in Dharmasraya Regency is still carried out manually through screening, and other issues, such as inclusion and exclusion errors, can potentially lead to inaccurate targeting. This research aims to design and build a web-based Decision Support System (DSS). The system development process uses Waterfall, UML, and is implemented using the PHP programming language with a MySQL database. The Simple Additive Weighting (SAW) method successfully helps determine PKH recipients objectively and accurately. The SAW method is used to calculate the value of each alternative based on predetermined criteria weights, then produces a ranking of potential recipients. The research stages include data collection through observation, interviews, literature and documentation studies, followed by needs analysis, system design, implementation, and testing using Black Box Testing. The results show that the system is able to minimize errors and subjectivity in determining beneficiaries.